The global role of G6PD in infection and immunity - Shah, Shivang S.; Stone, Elizabeth F.; Francis, Richard O.; Karafin, Matthew S. (Frontiers in Immunology, 2024)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzymopathy in humans. G6PD is an essential enzyme in the pentose phosphate pathway (PPP), generating NADPH needed for cellular biosynthesis and reactive oxygen species (ROS) homeostasis, the latter especially key in red blood cells (RBCs). Beyond the RBC, there is emerging evidence that G6PD exerts an immunologic role by virtue of its functions in leukocyte oxidative metabolism and anabolic synthesis necessary for immune effector function. We review these here, and consider the global immunometabolic role of G6PD activity and G6PD deficiency in modulating inflammation and immunopathology.